Tolerance Stack Analysis in Francis Turbine Design - Indra Djodikusumo; Koko Suherman; Paskalis Bowo A. Oken (Institute for Research and Community Services, Institut Teknologi Bandung, 2010)
The tolerance stacking problem arises in the context of assemblies from interchangeable parts because of the inability to produce or to join parts exactly according to nominal dimensions. Either the relevant part's dimension varies around some nominal values from part to part or the act of assembly that leads to variation. For example, as runner of Francis turbine is joined with turbine shaft via mechanical lock, there is not only variation in the diameter of runner and the concentricity between the runner hole and turbine shaft, but also the variation in concentricity between the outer parts of runner to runner hole. Thus, there is the possibility that the assembly of such interacting parts won't function or won't come together as planned. Research in this area has been conducted and 2 mini hydro Francis turbines (800 kW and 910 kW) have been designed and manufactured for San Sarino and Sawi Dago 2 in Central Sulawesi. Experiences in analyzing the tolerance stacks have been documented. In this paper it will be demonstrated how the requirements of assembling performance are derived to be the designed tolerances of each interacting component, such a way that the assembling would be functioning and come together as planned.